2017
DOI: 10.2147/copd.s124547
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen coadministration slows the development of COPD-like lung disease in a cigarette smoke-induced rat model

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a progressive pulmonary disease caused by harmful gases or particles. Recent studies have shown that 2% hydrogen or hydrogen water is effective in the treatment and prevention of a variety of diseases. This study investigated the beneficial effects and the possible mechanisms of different hydrogen concentrations on COPD.MethodsA rat COPD model was established through smoke exposure methods, and inhalation of different concentrations of hydrogen was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Therefore, how to improve the bronchial mucosal immunity is a core issue. Our previous study showed that hydrogen inhalation could visibly reduce inflammation and apoptosis, and improve cardiovascular function, suggesting a "significant effect" of hydrogen inhalation on COPD (21). Our results provided new information that treatment with hydrogen could ameliorate pathological changes, airway remodeling as well as SIgA expression.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, how to improve the bronchial mucosal immunity is a core issue. Our previous study showed that hydrogen inhalation could visibly reduce inflammation and apoptosis, and improve cardiovascular function, suggesting a "significant effect" of hydrogen inhalation on COPD (21). Our results provided new information that treatment with hydrogen could ameliorate pathological changes, airway remodeling as well as SIgA expression.…”
Section: Discussionsupporting
confidence: 57%
“…In recent years, a number of studies have shown that hydrogen therapy has a positive effect on various diseases (17)(18)(19)(20). Liu et al in our team found that different concentrations of hydrogen inhalation could significantly reduce inflammation and apoptosis, protect mitochondria, and ameliorate cardiovascular function in COPD rat model (21). A key question is whether there exist a possibility that hydrogen inhalation will have a positive effect on SIgA expression in rat model of COPD , which is to be tested in the experiment.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, H 2 can be produced conveniently (e.g., in an ambulance) and inexpensively by electrolyzing water. H 2 generator is a novel equipment and has reportedly been used in renal calcium oxalate deposition [9], cerebral ischemia-reperfusion injury [10], liver ischemia-reperfusion injury [11], chronic obstructive pulmonary disease model rats [12], and sanitation workers exposed to haze [13], with promising outcomes in alleviating inflammation and biological safety. However, data on clinical use of H 2 in patients with tracheal stenosis remain so far insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…; Liu et al. ). Though, these studies did not include an in‐depth look into the different membrane structures.…”
Section: Discussionmentioning
confidence: 98%